The Effect of Composition and Type of Metal Filler on Heat Resistance of Silica Rubber Matric Composites - R.N. Akhsanu Takwim; Anggit Murdani; Purwoko; Bayu Pranoto; Naufal Reza Putra (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
Thermal Tensioning is one of the methods use to minimise the occurrence of residual stress and unwanted distorsion during welding. One of the thermal tensioning methods is Static Thermal Tensioning (STT), which involves countering thermal stress during welding. The STT method requires an active cooling behind the welding line. Several properties are required for the coolant material, such as thermal conductivity, heat resistance, and good flexibility. To achieve the desired properties, a mixture of different materials was used, commonly called a composite. The purpose of this study is to know the effect of filler metal composition and type on the heat resistance of silica rubber matric composites. This study used 2 independent variables: the filler composition in composites with variations of K1 (60%) and K2 (70%), and the type of filler metal, aluminium and copper powder with variation J1 (100%-0%), J2 (75%-25%), J3 (50%-50%), J4 (25%-75%), and J5 (0-100%). The testing process used Thermogravimetry Analysis (TGA) method with replication 2 times. The results of this study showed the specimens with K1;J1 composition,containing 60% pure aluminium filler metal, showed the best heat resistance with a final weight of 88,25%. While specimens with K2;J5 composition, containing 70% pure copper filler metal, showed the worst heat resistance with a final weight of 74,25%.